2021
DOI: 10.3390/designs5010009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, Design, and Comparison of Machine-Learning Techniques for Networking Intrusion Detection

Abstract: The use of machine-learning techniques is becoming more and more frequent in solving all those problems where it is difficult to rationally interpret the process of interest. Intrusion detection in networked systems is a problem in which, although it is not fundamental to interpret the measures that one is able to obtain from a process, it is important to obtain an answer from a classification algorithm if the network traffic is characterized by anomalies (and hence, there is a high probability of an intrusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Some recent works as [1]- [3] use the ML and AIbased methodologies to explore the various ways of detecting malicious attacks in the computer's networks. In other works in literature for cybercrime [4]- [7], it has been already demonstrated that ML and AI-based methodologies have the potentiality to outperform rules-based IDS tools, such as SNORT and WIRE-SHARK. This is mainly due to the flexibility of ML/AI models.…”
Section: A Motivationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent works as [1]- [3] use the ML and AIbased methodologies to explore the various ways of detecting malicious attacks in the computer's networks. In other works in literature for cybercrime [4]- [7], it has been already demonstrated that ML and AI-based methodologies have the potentiality to outperform rules-based IDS tools, such as SNORT and WIRE-SHARK. This is mainly due to the flexibility of ML/AI models.…”
Section: A Motivationsmentioning
confidence: 99%
“…In addition, many works limit themselves to testing their algorithms on a single dataset, limiting the validity of the achieved results. For example, in [4], the authors mainly analysed the problem of binary classification on a single dataset. This obviously requires a priori knowledge of anomalous and normal traffic.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, mixed criticality comes into play by defining different constraints and thresholds on tolerated faults for the diverse network participants, e.g., see [34]. Further techniques include one-class classifiers, which can detect anomalies in communication systems [37], and machine learning, e.g., for intrusion detection [38].…”
Section: B the Mape Scheme In Communicationsmentioning
confidence: 99%
“…It is assumed in this algorithm that in multidimensional space, every instance resembles other points. The Euclidean distance is used to evaluate the nearest neighbor of any instance along with recalculating the new group "k" points [4,5]. To find the nearest distance, we repeat this strategy until the "k" point selection.…”
Section: Introductionmentioning
confidence: 99%